Association of complete blood count parameters, d‐dimer, and soluble P‐selectin with risk of arterial thromboembolism in patients with cancer. (17th June 2019) - Grilz, Ella; Marosi, Christine; Königsbrügge, Oliver; Riedl, Julia; Posch, Florian; Lamm, Wolfgang; Lang, Irene M.; Pabinger, Ingrid; Ay, Cihan
Abstract: Background: Patients with cancer are at risk of developing arterial thromboembolism (ATE). With the prevalence of cancer and cardiovascular diseases on the rise, the identification of risk factors for ATE in patients with cancer is of emerging importance. Objectives: As data on the association of potential biomarkers with risk of ATE in patients with cancer are scarce, we conducted a cohort study with the aim to identify blood‐based biomarkers for ATE risk prediction in patients with cancer. Patients/Methods: Overall, 1883 patients with newly diagnosed cancer or progressive disease after complete or partial remission were included and followed for 2 years. Venous blood was drawn at study inclusion for measurement of complete blood count parameters, total cholesterol, d‐dimer, and soluble P‐selectin (sP‐selectin) levels. Results: The 2‐year cumulative incidence of ATE was 2.5%. In univariable analysis, red cell distribution width (subdistribution hazard ratio (SHR) per doubling: 4.4, 95% CI: 1.4‐14.1), leukocyte count (1.2, 1.1‐1.5), neutrophil count (1.6, 1.1‐2.3), and sP‐selectin levels (1.9, 1.3‐2.7) were associated with risk of ATE in patients with cancer; d‐dimer was not associated with the risk of ATE (1.1, 0.9‐1.4). After adjustment for age, sex, and smoking status the association prevailed for the neutrophil count (adjusted [adj.] SHR per doubling: 1.6, 1.1‐2.4), and sP‐selectin levels (1.8, 1.2‐2.8). Conclusions: An elevated absolute neutrophil count and higher sP‐selectin levels were associated with an increased risk of ATE in patients with cancer. Their role for predicting cancer‐related ATE needs to be validated in further studies.